Interpretation of Verses About Education - Salman; Iskandar Mirza (Classroom: Journal of Islamic Education, 2025)
Islamic education integrates the acquisition of knowledge with the development of character in accordance with religious teachings. Allah SWT's command to seek knowledge, as revealed in Surah Al-Alaq, emphasizes both worldly and spiritual knowledge. Islamic education is a lifelong obligation for all Muslims, regardless of age or gender, and must be applied in daily life to benefit individuals and society. This paper utilizes Library Research methodology, reviewing tafsir books and relevant literature to explore Islamic education from the Quranic perspective. Knowledge, both religious and secular, is valued in Islam, with scholars being regarded as the inheritors of the prophets. Islamic education is holistic, encompassing physical, mental, and spiritual development, and aims not only to educate but also to cultivate good character. Therefore, students are encouraged to pursue and apply knowledge earnestly in their lives.